Pearson Discover History student book 2 - Nick Tapp; Nick Tapp (Karachi Kifayat publisher, 2024)
The Pearson Discover History Book 3 for Class 8 is designed to engage middle school students in Pakistan with a comprehensive and interactive approach to learning history.
Keywords: Book